Determination of Haze API From Forest Fire Emission During the 1997 Thick Haze Episode in Malaysia using NOAA AVHRR Data - Ahmad, Asmala (2000)
The results of a study conducted at the UTM Centre for Remote Sensing is reported to quantify haze from forest fire emission using NOAA AVHRR data. In this study, NOAA AVHRR LAC data dated 22 September 1997, one of the worst thick haze episode in Malaysia were used. The relationship between measured Air Pollution Index (API) of the measurements were carried out by Alam Sekitar Malaysia Sdn. Bhd. (ASMA) at five selected air pollution stations in Peninsular Malaysia. These relationships were shown as the best regression model. Finally, these models were used in generating maps of haze-intensity for individual haze components, namely carbon monoxide (CO), Ozone (O3), PM10, sulphur dioxide (SO2) and nitrogen dioxide (NO2) in order to predict haze API from NOAA AVHRR data. The results indicated that NOAA AVHRR data are very useful in reporting regional haze occurrence continuously.